Agroecology - Pilipavičius, Vytautas (IntechOpen, 2015)
This book is a collection of chapters, concerning the developments within the Agroecology field of study. The book includes scholarly contributions by various authors pertinent to Agricultural and Biological Sciences. Each contribution comes as a separate chapter complete in itself but directly related to the book's topics and objectives. The target audience comprises scholars and specialists in the field.